PENGARUH VARIABEL EKONOMI, SPEKULASI PASAR DAN KEBIJAKAN MONETER TERHADAP HARGA TRANSAKSI PROPERTI PERUMAHAN DI WILAYAH PERKOTAAN DI INDONESIA - BASUKI PARTAMIHARDJA (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2015)
Transactions occur as a result of interaction between the two groups of market participants, thepotential buyers (non-owners) on the demand side, and potential sellers (owners) on the supplyside. Behavior of residential property transactions differ between regions both nationally,regionally and in the world. Transaction behavioral for housing property has some differencesbetween regions both nationally, regionally and in the world. This study aims to understand thetransaction price for housing properties as well as the factors that influence. Transaction pricefor housing properties are also reviewed based on class market segment of small, medium andlarge. Government’s policyies have also seen the impact on transaction price for housingproperty.The reserch was conducted in 10 major city in Indonesia based on housing property survey dataconducted by Bank Indonesia and BPS for 8 years (2003-2010). Transaction price for housingproperties as well as the factors that influence were analyzed through regression analysis ofpanel data, while interest rate policy analysis through simulation analysis.Generally, this research found that the transaction price for housing properties is influenced byinterest rates, income and speculative factors. Interest rates and income more effect totransaction price for smaller housing types, followed by middle type and large type. Marketspeculation factor more effect to transaction price for large housing types, followed by smallertype and middle type. The influence of the type of speculation on house purchases indicate atendency not to live alone (use value) but for rent or sale at a later time (transfer value). Themonetary instruments by interest rate policy to control the transaction price for housing throughinterest rate subsidies or down payment subsidies to encourage home ownership for people,especially for the lower middle class.Key-words: quantity of housing property transaction, segment of property, region, speculation